2004
DOI: 10.1051/apido:2004037
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in honeybee (Apis mellifera) larvae treated with oxalic or formic acid

Abstract: -The effects of oxalic (OA) and formic acids (FA) on honeybee larvae in colonies were assessed and evaluated. Cell death was detected by the TUNEL technique for DNA labelling. In 3-and 5-day-old larvae exposed to OA, cell death was found in 25% of midgut epithelial cells 5 h after the treatment, using an "In situ cell death detection kit, AP" (Roche). The level of cell death increased to 70% by the 21st hour and the morphology of the epithelium remained unchanged. Fifty hours after the application, cell death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…Normal cell turnover usually ranges between 5% and 10% (Gregorc and Bowen, 1997;Gregorc et al, 2004) which is consistent with the 8% cell death found in the control tissue when using a DeadEnd kit. Using an ISCDDK assay Gregorc and Bowen (2000) found that amitraz -another acaricide -increased the level of cell death in bee larvae and that an OA application triggered necrotic cell death in the midgut (Pulkkanen et al, 2000).…”
Section: Cell Deathsupporting
confidence: 75%
See 1 more Smart Citation
“…Normal cell turnover usually ranges between 5% and 10% (Gregorc and Bowen, 1997;Gregorc et al, 2004) which is consistent with the 8% cell death found in the control tissue when using a DeadEnd kit. Using an ISCDDK assay Gregorc and Bowen (2000) found that amitraz -another acaricide -increased the level of cell death in bee larvae and that an OA application triggered necrotic cell death in the midgut (Pulkkanen et al, 2000).…”
Section: Cell Deathsupporting
confidence: 75%
“…Programmed cell death in honeybees (Apis mellifera L.) has been revealed in the regressive hypopharyngeal glands (Moraes and Bowen, 2000) and in the midgut after a Paenibacillus larvae infection and an application of the acaricide amitraz Bowen, 1998, 2000) as well as in the isolated atria of the heart after exposure to the herbicide 2,4-Dichlorophenoxyacetic acid (Papaefthimiou et al, 2002). It has also been shown that an OA solution becomes distributed throughout the digestive system of an adult worker bee within 24 h (Nanetti et al, 2002;Nozal et al, 2003) and, when applied directly onto bee larvae, has an adverse effect on the midgut at the cellular level (Gregorc et al, 2004). Investigations into the effects of OA and rotenone at the tissue and cellular level are important in order to monitor their modes of acaricidal action and to study any preclinical symptoms, as their introduction into a honeybee colony may cause injury to its population and, therefore, negatively impact upon its development.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly fewer cells containing sealed brood were reported in treated colonies compared to the control groups (Wilcoxon-Mann-Whitney-test, P < 0.05; Higes et al, 1999). The effect of oxalic acid on bee larvae was investigated by Gregorc et al (2004). A solution of 6.5 g oxalic acid dihydrate / 50 g sugar/ 100 mL water sprayed on honey bee larvae (0.121 mg / larvae) affected the columnar cells of the midgut, leading to necrosis.…”
Section: Tolerabilitymentioning
confidence: 99%
“…The measured formic acid concentrations in the atmospheres of the laboratory trials of ≥160 ppm would have been effective against varroa mites within beehives (Imdorf 2005). Values of ≥680 ppm would cause severe impacts on honeybee colonies, such as disorientation of bees (Przewozny et al 2003), queen loss, and/or dead brood (Gregorc et al 2004). Such concentrations should therefore not be applied in a colony.…”
Section: Laboratory Experimentsmentioning
confidence: 99%